(untitled) (Heritage, 2022)
This paper presents the results of the analysis of the content related to the knowledge of traditional culture in the current curricula for the first cycle of primary education. Primary education in the Republic of Serbia is divided into two cycles with four grades each. In the first cycle there is class teaching, and in the second there is subject teaching. This analysis includes curricula, as well as their amendments, in the period from 2004 to the end of 2021. In these amendments, the contents of traditional culture have been constantly in various stages of change, adapting to changes in the ruling system of social values, the processes of interculturalism and globalization. The main starting point in this paper, which was confirmed after the research, is that in the curricula can be identified content related to knowledge of traditional culture, such as: language, values, moral principles, customs, folklore, beliefs, myths , legends, rituals and ceremonies. These contents are especially represented in the following subjects: Serbian language, Music culture, Religious education, Folk tradition and Mother tongue with elements of national culture, and then to a lesser extent in other subjects, such as: The world around us (first and second grade), Nature and Society (third and fourth grade), Art Culture and Physical Education. The goals of teaching in these subjects are mainly: acquiring knowledge of folk traditions, preserving national and religious identity, nurturing the traditions and culture of Serbian and other peoples living in the Republic of Serbia, adopting the spiritual values of the church or community to which they historically belong and developing interculturality. The importance of traditional culture in the curriculum for the first cycle of primary education is great, because through them students gain knowledge about the cultural and spiritual values of the community to which they belong and, at the same time, strengthen their personal, ethnic, religious and national identity. identities.